A formação dos professores no curso normal superior na perspectiva pós-LDBEN : um balanço crítico - Silva, Márcio Antônio (2008)
The purpose of this study is to examine the participation of the State University of Montes Claros (UNIMONTES) in the context of education policies of the country as regards its participation and proposition of training teachers in the Superior Normal mode in the post- LDBEN. Delineamos object of study as the training of teachers of the course Normal Superior / Modular offered by UNIMONTES. I reviewed the theoretical assumptions and economic education in the proposals of neoliberal Miltom Friedrick Hayek and Friedman. This study if it bases on the contributions of Karl Marx. The methodology is guided by qualitative research-quantitative, combining data: questionnaires, interviews, official documents of the course Normal Superior, matches of students and production of texts. The considerations possible, this research is that UNIMONTES, contributed to the access of a significant contingent of teachers of elementary school, following the decisions of LDBEN 9394/96. However, the university changes its role in training teachers when relegates to the background the course of teaching that has historical tradition in the training of professional education in the north of Minas.